Wide band ridge gap waveguide (RGW) fan beam antenna with low side lobes based on parabolic reflector principle. Issue 5 (28th January 2020) - Sabbaghi, Elham; Razavi, Seyed Ali; Ostovarzadeh, Mohammad Hossein
Abstract : In this paper, a wide band ridge gap waveguide (RGW) fan beam antenna with low side lobe level (SLL) is presented making use of parabolic offset reflector concept in antenna geometry. In the proposed topology, in contrast to TEM based RGW horn, the amplitude distribution across the antenna aperture can be easily controlled. Furthermore, thanks to intrinsic feature of parabolic reflector in generating plane wave front, the phase distribution uniformity across the proposed antenna aperture is better than that of the RGW horn. These two facts allow the proposed topology to provide lower SLL compared to the RGW horn. A prototype of the proposed structure is designed and fabricated. Simulation and measurement results also show that wider operating bandwidth compared to the RGW horn can also be achieved using this topology. For the designed sample, the impedance bandwidth of 41% with −20 dB ≤ SLL ≤ − 15 dB and gain of 11.8–15.5 dBi is achieved. Results show that the proposed topology can be a good candidate for realization of high gain wide band RGW fan beam antennas with low SLL.